The Basis and Possibility of Students’ Participation in Supply Chain Entrepreneurship (Case Study: Primorsky Territory) - Victor A. Osipov; Marina E. Vasilenko; Nataliya Yu. Titova (International Journal of Supply Chain Management, 2018)
Abstract- The current stage of development of the Russian economy, indicated by the increase in food sanctions, unemployment and the decline in growth rates, requires the introduction of import substitution mechanisms and a significant strengthening of the national entrepreneurship environment. Youth entrepreneurship plays a special role in the development of Russian small and medium-sized businesses. At the strategic and legislative levels, various programs are developed to support small business in this area. However, there are still some barriers, limiting the spread of small and medium-sized business among young people. In this regard, the problem of agitation of entrepreneurship among young people is important. This article presents the results of selective study, in which the supply chain entrepreneurial climate among the students of higher educational institutions of Primorsky Territory, using the method of sociological survey. The readiness of young people to start their own business was analysed, and unfavourable factors, complicating the development of this process, were identified. The authors defined key competences, determining the entrepreneur. The conclusion was made about the need for development, and necessary measures of state support for youth supply chain entrepreneurship. Keywords- supply chain entrepreneurship, Primorsky Territory, business incubator, small business, young people, Russia.